2010
DOI: 10.1595/147106710x523698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Platinum and Platinum-Cobalt Catalysts on Stability Against Load Cycling

Abstract: To investigate the effect of load cycling, platinum (Pt) and platinum-cobalt (PtCo) fuel cell catalysts with different particle sizes were prepared and evaluated for their durability against load cycling. The particle size of the Pt and PtCo catalysts was controlled by changing the catalyst loading and by applying heat treatment. Pt catalysts with particle sizes of 2–3 nm and 4–5 nm and PtCo catalysts with sizes of 3–4 nm, 4–5 nm and 7–8 nm were obtained. A potential sweep from 0.65 V to 1.05 V was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 0 publications
0
60
0
Order By: Relevance
“…• C, 23,26,34 we intend to clarify the effect of crystal structure on the ORR activity and durability for the Pt 3 Co alloy catalysts with the nearly identical size distribution. To suppress the excessive agglomeration of particles (< ca.…”
Section: Resultsmentioning
confidence: 99%
“…• C, 23,26,34 we intend to clarify the effect of crystal structure on the ORR activity and durability for the Pt 3 Co alloy catalysts with the nearly identical size distribution. To suppress the excessive agglomeration of particles (< ca.…”
Section: Resultsmentioning
confidence: 99%
“…The recent work by Matsutani et al reported particle size effects of the Pt and PtCo catalyst performance in MEAs and suggested that the MEAs with cathodes containing 4-5 nm Pt particles and 7-8 nm PtCo particles were the most stable. These two sizes were the largest of the catalyst particles studied [30]. These catalysts were found to be more stable when heat treated to a higher temperature.…”
Section: Introductionmentioning
confidence: 90%
“…doi:10.1016/j.apcatb.2011.10.007 electrocatalyst durability in PEMFCs, however, fewer studies have been reported. Matsutani et al [25] observed an improved stability of Pt against PEMFC load cycling as the Pt particle size increased from 2-3 nm to 4-5 nm after heat treatment, but detailed mechanism for the stability improvement was not addressed. Based on the literature, a comprehensive investigation with well-defined preparation and evaluation methodologies regarding Pt particle size effect on the activity for ORR and the durability of Pt/C in PEMFCs is yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%